Self-reported and performance-based measures of executive functions in interned youth - Nordvall, Olov (Psychology, crime & law, 2017)
This study address three questions: (a) Do interned adolescents exhibit general or specific deficits in the core executive functions, as compared to an age-matched control group? (b) Do interned adolescents report more executive problems in everyday life, as compared to an age-matched control group? And (c) are performance-based measures of executive functions related to self-reported executive problems? Thirty-one interned youths and 40 non-interned controls participated in the study. To this end, we measured the three constituents (inhibition, shifting, and updating) of the Unity/Diversity model of executive functioning, as well as the participants’ self-reported everyday executive functioning using the Behavior Rating Inventory of Executive Functions scale. The interned group performed less well compared to the control group on the majority of performance-based tasks but did not show more pronounced deficits in any one executive function, reflective of a more general deficit. Compared to the controls, the interned adolescents also reported more dysfunction in executive behaviors related to the ability to inhibit action, behavioral flexibility, working memory, and the ability to follow through with tasks. Overall, correlations between self-report and performance-based measures were weak. These findings suggest that performance-based and self-report measures may assess different, albeit important, aspects of executive functioning.